Deepening Integration in Border Regions within CAREC : The Asiaregio - World Bank (Washington, DC, 2014)
The central endeavor of Central Asia Regional Economic Cooperation (CAREC) is the deepening of cooperation between its members across the entire range of development activities. Recent papers prepared by the World Bank for consideration of the ministers and officials of CAREC countries have focused on fostering cooperation in border trade and in supporting key institutions that underpin border trade such as bazaars in central Asia. But cooperation in border areas goes much deeper than trade alone. Economic development activities related to trade such as tourism, retail, business and trade facilitation as well as cooperation in public services (such as shared health facilities, other infrastructure services such as small-scale irrigation), optimal use of the environment, cultural and sports activities often have a significant cross-border character. Therefore, cross-border arrangements that support such activities and realize economies of scale in the provision of services can yield high dividends; and the key public policy question is how to best make such arrangements flourish. This paper presents initial thinking on this question, responding to the request made by CAREC representatives. It is based on discussions with officials in Kazakhstan, Kyrgyzstan and Tajikistan in 2008-09 and on an examination of legal acts pertaining to cross-border cooperation.